PENERAPAN PEMBELAJARAN TEMATIK TEMA 2 KEGEMARANKU KELAS I A DI MI HIDAYATUL MUBTADIIN TASIKMADU - Astuti Astuti; Devi Wahyu Ertanti; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
This research is motivated by the lack of methods for thematic learning theme 2 about "my hobby" which is applied by the teacher to students in class. some students still find it difficult to carry out an experiment and still have difficult understanding and accepting the material presented by the teacher on thematic learning. This study aims to see the application of thematic learning theme 2 "my passion" which is applied to class I A through the demonstration method. The research approach carried out in this research is qualitative research type case studies. Based on the results of research using the demonstration method students can learn independently, try directly and can be creative according to the abilities of students. Under the application of  demonstration method to thematic learning the  students' average results above the KKM which criterion is 75. The specific constraints experienced by the teacher in applying thematic learning is the terms of infrastructure in the classroom, and the teacher's health so that the implementation of learning is less effective and there are some students who are active in class. Teacher solutions for  the application of thematic learning  is the teacher should apply   that are appropriate to students and varies, mastery of the material by the teacher.